(untitled) - Leana Uys; Sue Cameron; eds (Oxford,New York, 2003)
A textbook aimed at nurses working with and in the homes of people with AIDS. Also useful to the family and friends of a person with AIDS
Includes bibliographical references and index
Keywords: HIV-positive persons; Home nursing; AIDS (Disease); AIDS (Disease)